Gambaran Activity Daily Living (ADL) Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis di RS Setia Mitra Jakarta - Farahdina Bachtiar; Purnamadyawati Purnamadyawati (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: In many studies, patients with Chronic Kidney Disease (CKD) who undergoing Hemodialysis (HD) have been evident to have low levels of physical functioning as well as difficulty performing activities of daily living (ADL) compared to the healthy population. This study aims to describe the activities of daily living performance among CKD patients with HD. Methods: Subjects were 42 CKD outpatients (27 men, 15 women; mean age 50 ± SD=9,49) undergoing maintenance HD one to two times a week. This study employed a cross-sectional descriptive study design. Data were collected from September to October 2020 in Setia Mitra Hospital, Jakarta, Indonesia. Assessment of Activity Daily Living (ADL) was administered using the Katz Index.Result: In this study, we assessed six items of patient’s functional status including bathing, dressing, toileting, transferring, continence, and feeding. The majority of participants (33 people, 79%) had complete independence in performing activities of daily living. However, there were 9 participants (21%) who still need assistance in performing activities of daily living. Conclusion: Although this study found that most participants did not have difficulty in ADL, some participants reported that they needed assistance while performing ADL. Physiotherapy is an important element in the management of CKD patients with HD. The physiotherapy program can help to improve patient’s health, independence in carrying out activities of daily living, reduce stress and depression, improve self-esteem as well as quality of life.